Manajemen Lembaga Pendidikan Berorientasi Mutu di SMP Ali Maksum Krapyak Yogyakarta - Achmad Sunani Miftachurrohman; Atika Atika (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
AbstractThe quality of education is about two sides of a very important process and results. Quality in the educational process involving various inputs such as; learning materials (cognitive, affective, or psychomotor), methodology (vary according the ability of teachers), educational institutions and infrastructure, administrative support, a variety of resources and efforts of the creation of a fair and convenient to learn. Quality in the context of